A theoretical investigation of erbium‐doped fiber laser as a function of ion‐clustering, temperature, pumping wavelength, and configuration. Issue 2 (6th October 2019) - Kabir, Md. Aminul; Hossain, Md. Mahbub; Amin, Md. Ziaul; Ahsan, Md. Shamim
Abstract: The lasing performance of an erbium‐doped fiber laser (EDFL) is affected by several factors such as doping concentrations, erbium‐ion clustering, pumping wavelength, pumping configuration, and temperature. In this article, the performance of an EDFL has been investigated as a function of erbium‐ion clustering, pumping wavelength, pumping configuration, and temperature. In our investigation, we have found that power degradation, which happens due to ion‐clustering, at around 1530 nm is less affected for 980 nm pumping than for 1480 nm pumping. Moreover, a wider tuning range is achieved for 980 nm pumping than 1480 nm pumping. Our simulation results also show that the forward pumping configuration is suitable for a wider tuning range. To our best knowledge, pumping wavelength and configuration effects on an EDFL performance have not been investigated yet. We have also investigated the temperature effects on an EDFL performance and found little influence on lasing performance, at least within 30°C to 80°C.